2017
DOI: 10.1007/s10916-017-0855-8
|View full text |Cite
|
Sign up to set email alerts
|

On Applicability of Tunable Filter Bank Based Feature for Ear Biometrics: A Study from Constrained to Unconstrained

Abstract: In this paper, an overall framework has been presented for person verification using ear biometric which uses tunable filter bank as local feature extractor. The tunable filter bank, based on a half-band polynomial of 14th order, extracts distinct features from ear images maintaining its frequency selectivity property. To advocate the applicability of tunable filter bank on ear biometrics, recognition test has been performed on available constrained databases like AMI, WPUT, IITD and unconstrained database lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…The ear recognition field has witnessed an increasing interest during the last few years and nearly perfect recognition rates have been attained under constrained conditions [24], [25], [26], [27]. The proposed techniques were developed and evaluated using small ear datasets gathered under laboratorylike settings with limited variations in lighting, head poses and occlusions.…”
Section: Related Workmentioning
confidence: 99%
“…The ear recognition field has witnessed an increasing interest during the last few years and nearly perfect recognition rates have been attained under constrained conditions [24], [25], [26], [27]. The proposed techniques were developed and evaluated using small ear datasets gathered under laboratorylike settings with limited variations in lighting, head poses and occlusions.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we review traditional ear detection methods along with CNN‐based detection methods. Emeršič et al and Chowdhury et al thoroughly reviewed the techniques in literature for automatic ear detection and recognition. These survey papers also included the benchmark datasets for ear recognition research.…”
Section: Related Workmentioning
confidence: 99%
“…The planes of projection are divided into L × L bins and a distribution matrix is computed by counting the number of points falling in each bin. Furthermore, for the obtained distribution matrix, lower-order central moments μ 11 , μ 12 , μ 21 , μ 22 (6), and entropy e (7) is computed to form a feature vector. Given a distribution matrix D, the central moment μ mn can be defined as follows:…”
Section: D Feature Descriptormentioning
confidence: 99%
“…Although ear has rich and unique characteristics, fast and accurate recognition of the ear is still a challenging task. Although in the literature, there exist several works on constrained and unconstrained ear recognition [6][7][8][9][10], the practical use of 2D ear recognition in real applications is still a hurdle due to its poor recognition accuracy. It is found that poor recognition accuracy due to common problems such as pose variations, illumination, and scaling is easily overcome by threedimensional (3D) images.…”
Section: Introductionmentioning
confidence: 99%